2013
DOI: 10.1155/2013/253657
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Heart Failure and Cardiometabolic Complications in Obesity May Be Masked by an Apparent Healthy Status of Normal Blood Glucose

Abstract: Although many obese individuals are normoglycemic and asymptomatic of cardiometabolic complications, this apparent healthy state may be a misnomer. Since heart failure is a major cause of mortality in obesity, we investigated the effects of heme-oxygenase (HO) on heart failure and cardiometabolic complications in obese normoglycemic Zucker-fatty rats (ZFs). Treatment with the HO-inducer, hemin, reduced markers of heart failure, such as osteopontin and osteoprotegerin, abated left-ventricular (LV) hypertrophy/f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
1
5
0
2
Order By: Relevance
“…Moreover, our recent findings indicate that the suppression of pericardial adiposity is associated with improved cardiac function. 35,64 Hemin also enhanced HO-1, HO activity, and the total antioxidant capacity in ZL-control rats and correspondingly reduced pericardial adiposity, 8-isoprostane, TNF-a, IL-6, IL-1b, and fasting glucose. However, the magnitude of hemin effects on ZL controls was smaller as compared to ZFs with aberrant HO-1 and HO activity.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, our recent findings indicate that the suppression of pericardial adiposity is associated with improved cardiac function. 35,64 Hemin also enhanced HO-1, HO activity, and the total antioxidant capacity in ZL-control rats and correspondingly reduced pericardial adiposity, 8-isoprostane, TNF-a, IL-6, IL-1b, and fasting glucose. However, the magnitude of hemin effects on ZL controls was smaller as compared to ZFs with aberrant HO-1 and HO activity.…”
Section: Discussionmentioning
confidence: 88%
“…Immunohistochemistry was done as we previously described [15,18,26,29] . Sections of 5 µm of whole kidney were treated with bovine serum albumin in phosphate buffered saline to avoid non-specific staining and incubated overnight with ED1 antibody (1:5 dilution, Santa Cruz Biotechnology, CA), and subsequently with goat anti-mouse IgG for 30 min (1:200 dilution; Jackson ImmunoResearch Laboratories, Inc., ME, USA).…”
Section: Methodsmentioning
confidence: 99%
“…13 It was reported that increased levels of TNF-α in hearts from diabetic rodents is significantly correlated with development of LV dysfunction and is negatively correlated with degree of contractility. [38][39][40][41] This cytokine is also responsible for perturbations in cardiomyocyte metabolism given its negative effect on the intracellular cascade triggered by activation of insulin receptor. 32 In the current study, LASSBio-2090 normalized the upregulation of TNF-α in the heart tissue from ZDF rats with DC and this was reflected in improved LV function in vivo as depicted by the normalization of contractility and compliance and reduction in cardiac remodeling.…”
Section: Collagen Fractional Area (%)mentioning
confidence: 99%